Effect of different cropping options on plant-available water of surface-drained Vertisols in the Ethiopian highlands - Astatke, A.; Mohamed-Saleem, M.A. (Elsevier, 1998)
The productivity of the Vertisols in the Ethiopian highlands could be raised by facilitating the removal of excess water from the field in the main rainy season. This could be accomplished by the introduction of an animal powered broadbed maker (BBM) which shapes the soil into broadbeds and furrows. Thus with proper drainage, early sowing of crops becomes feasible. This study compared the plant-available water in the soil layer and the water use efficiency of local wheat and eight other cropping options and also assessed the grain and fodder productivities. Replacing late-sown local wheat with an early-sown improved wheat variety (ET-13) improved the utilization of the plant-available water during the rainy season and significantly increased grain and straw yields with a high rate of water use efficiency. The variations of the available mositure in the soil layer between the different cropping options tested were small during the rainy months of July and August due to the continuing replenishment of the used water. Differences of plant-available water in both upper and lower soil layers for the various cropping options became distinct at the onset of the dry season. Even though results showed that growing of a sequential crop, such as grass pea, following wheat is possible with a starter irrigation in the dry season, yields were generally depressed.